D.P.F Delphi AndroidNative Components: A Framework for Native Android Development with Delphi XE5 - Yaghobi, B (Journal Dekstop Application (JDA), 2025)
The development of Android applications using Delphi XE5 and the D.P.F AndroidNative Components represents a significant step in unifying traditional desktop programming with the demands of modern mobile computing. This research explores how Delphi’s object-oriented and component-based design can be extended to the Android environment through native integration using the Java Native Interface (JNI) and Android NDK. The study begins by outlining the technical architecture of Delphi XE5, emphasizing the FireMonkey framework, JNI bridging, and SDK interoperability. It continues with an overview of the D.P.F AndroidNative Components library, which provides Delphi-accessible wrappers for core Android widgets and APIs such as buttons, lists, dialogs, and system services. Through a structured development workflow—covering environment configuration, UI design, event-driven programming, and deployment—the framework enables developers to create fully native Android applications using Object Pascal while maintaining Delphi’s familiar development model. Experimental implementation demonstrates that applications built with D.P.F components achieve native performance, efficient memory handling, and seamless interaction with Android system features. Compared with other cross-platform frameworks like Flutter or Xamarin, D.P.F offers a unique balance of native execution and Delphi’s rapid application development efficiency. Although challenges remain, including limited maintenance and partial component coverage, the framework proves valuable for developers and educators aiming to extend Delphi’s potential into the Android domain. The study concludes that D.P.F AndroidNative Components not only reaffirm Delphi’s adaptability in the evolving mobile ecosystem but also highlight the importance of community collaboration, open-source sustainability, and cross-paradigm learning in software development.